EL USO DE PARAGUAS COMO BIEN COMÚN EN LA UNIVERSIDAD DE COSTA RICA - Casafont Terán, María Victoria (2012)
This work, done as a practice Psychology and Environment Module of the School of Psychology at the University of Costa Rica, aimed to analyze the use that the community college campus Rodrigo Facio gives to a common good, in this case the umbrella. Also focused on analyzing the type of rule which best meets the academic community for the use of common goods. For this, we performed a practice, that for three weeks had the interest to measure the effect of different types of rules: very specific, intermediate, and diffuse ones about the use of umbrellas. In total, 15 umbrellas were placed (5 new for weeks). To the end, were obtained 40% of the umbrellas. Hardin (1968), mentions that people are predisposed to expect what will happen, and there are abusers to get maximum individual utility of the common good, referring to the tragedy of the commons, however, the common good should not be a tragedy, should serve as resources that support sustainable community partnerships. This project is considered to be an excellent initiative for future projects, both on and off of the university campus.